Wet/dry accelerated laboratory test to simulate the formation of multilayered rust on carbon steel in marine atmospheres. (3rd April 2017) - Calero, J.; Alcántara, J.; Chico, B.; Díaz, I.; Simancas, J.; de la Fuente, D.; Morcillo, M.
ABSTRACT: The prolonged exposure of carbon steel in marine atmospheres with high chloride deposition rates and long times of wetness of the metallic surface leads to the formation of thick multilayered rust. The present work proposes an accelerated cyclic laboratory test based on immersion (4.2 min) in a 3.5% NaCl solution followed by drying (12 min) under infra-red lamps in the laboratory atmosphere. The carbon steel corrosion process is thus accelerated, giving rise to the generation of thick rust layers in relatively short times. The rust phases and the structure of the rust layers formed offer a good approximation to the multilayered rust formed in marine atmospheres. The study includes a gravimetric evaluation of the magnitude of corrosive attack and a characterisation of the rust phases and corrosion layers formed using XRD, optical microscopy and SEM.